(untitled) (Communication & Society, 2004)
Supported in a survey carried out by the Centro de Investigaciones Sociológicas to 1.787 Spanish families (E-2391 CIS), this article analyses their mediation styles from the children’s consumption of television. After carrying out a factorial analysis with which the main mediation strategies have been extracted, it has been applied an analysis of conglomerates of which a typology composed for controller- restrictive, permissive and guide families has arisen. Previously, the influence of several socio-demographic, familiar and of audiovisual equipment variables has been examined, in each one of the mediation strategies. The results allow to adapt with some tinges typologies elaborated in other countries.